Synthesis of Some New 4-Iodo Isoxazoles and Pyrazoles and Their Antimicrobial Activity - Heda, P.B.; Ghiya, B.J. (Asian Journal of Chemistry, 2010)
Various propane 1,3-diones-(β-diketones) (I) were synthesized. (I) on iodination by iodine monochloride in dioxane gave 2-iodo-propane-1,3- dione (II). (II) was condensed with hydroxylamine hydrochloride, hydrazine hydrate and phenyl hydrazine in ethanol to get 4-iodo-3,5-(sub) diphenyl isoxazoles (III), 4-iodo-3,5-(sub) diphenyl pyrazoles (IV) and 4-iodo-1,3,5-triphenyl pyrazoles (V) respectively. The structures of synthesised compounds were confirmed by elemental analysis, chemical properties and IR, NMR and mass spectral data. Antimicrobial activity of some of the synthesized compounds was also studied.